An Efficient deep learning approach to detect Brain Tumor using MRI images - Islam, Annur Tasnim; Apu, Sakib Mashra; Sarker, Sudipta; Hasan, Inzamam M.; Shuvo, Syeed Alam (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.